The effect of reserpine on sympathetic, purinergic neurotransmission in the isolated mesenteric artery of the dog: a pharmacological study. - Muramatsu, I. (1987)
Electrical transmural stimulation evoked a transient contraction in the isolated mesenteric artery of the dog. This contraction was abolished by guanethidine or tetrodotoxin and was partially inhibited by prazosin. Noradrenaline was competitively antagonized by prazosin. Similarly, in the reserpine-treated artery, electrical transmural stimulation produced a transient contraction which was abolished by guanethidine or tetrodotoxin. However, prazosin failed to inhibit this contraction. The contraction to noradrenaline was not significantly different from the response it produced in control vessels. Tyramine (10(-5) M), which acts on sympathetic nerves to release noradrenaline, evoked a tonic contraction in the untreated artery. This contraction was abolished or markedly attenuated by prazosin or guanethidine. The response was not observed in the reserpine-treated artery, indicating that reserpine had depleted the nerves of noradrenaline. In the control vessel alpha,beta-methylene-ATP produced a transient contraction which was followed by a complete relaxation to the basal level. This contractile response was not significantly different in the presence of guanethidine or prazosin or in the reserpine-treated artery. After desensitization of the vessel to alpha,beta-methylene ATP (5 X 10(-6) M) the prazosin-resistant contractions induced by electrical transmural stimulation were abolished both in reserpine-treated and untreated arteries. Also the contractile responses to ATP and alpha-beta-methylene-ATP were abolished but the responses to tyramine (control vessels), noradrenaline and KCl were not affected. 8-Phenyltheophylline (10(-5) M) showed no inhibitory effect on the contractile responses to electrical transmural stimulation, tyramine, ATP or alpha,beta-methylene-ATP.(ABSTRACT TRUNCATED AT 250 WORDS)